miR-139-5p Was Identified as Biomarker of Different Molecular Subtypes of Breast Carcinoma - Yan, Meidi; Sun, Haohang; Li, Guoqing (Frontiers in Oncology, 2022)
Located on chromosome 11q13.4, miR-139-5p has been confirmed by several studies as a possible attractive biomarker for cancer, including breast cancer, but its mechanism of correlation in different molecular subtypes of breast cancer has not been reported. In this study, comprehensive bioinformatics analysis was used to evaluate the expression of miR-139-5p in different molecular subtypes of breast cancer (luminal A, luminal B, HER2-enriched, and basal-like). The target genes of miR-139-5p were predicted by using an online database TargetScan and miRDB, and three key genes, FBN2, MEX3A, and TPD52, were screened in combination with differentially expressed genes in different molecular subtypes of breast cancer. The expression of the three genes was verified separately, and the genes were analyzed for pathway and functional enrichment. Bone marrow mesenchymal stem cells (BMSC) are another kind of highly plastic cell population existing in bone marrow besides hematopoietic stem cells. BMSC can affect the proliferation and migration of cancer cells, promote the metastasis and development of cancer, and regulate the tumor microenvironment by secreting exosome mirnas, thus affecting the malignant biological behavior of tumor cells. Finally, human bone marrow mesenchymal stem cells exosomes were obtained by ultracentrifugation, and the morphology of exosomes was observed by transmission electron microscopy. The expression of miR-139-5p in normal breast cells MCF-10A, human breast cancer cell line MDA-MB-231 cells, and BMSCs-derived exosomes were compared; the exosomes and MDA-MB-231 cells were co-cultured to observe their effects on the proliferation of the MDA-MB-231 cells. Human bone marrow mesenchymal stem cell-derived exosomes inhibited the growth of breast cancer cells and promoted the expression of FBN2, MEX3A, and TPD52 by transporting miR-139-5p.